Inequality and informality in transition and emerging countries - Roberto Dell'Anno (IZA World of Labor, 2021)
Higher inequality reduces capital accumulation and increases the informal economy, which creates additional employment opportunities for low-skilled and deprived people. As a result, informal employment leads to beneficial effects on income distribution by providing sources of income for unemployed and marginalized workers. Despite this positive feedback, informality raises problems for public finances and biases official statistics, reducing the effectiveness of redistributive policies. Policymakers should consider the links between inequality and informality because badly designed informality-reducing policies may increase inequality.
Keywords: D64; H41; J31; 330; informality; inequality; shadow economy